Dampak Penggunaan Air Irigasi Terhadap Sifat Fisika Dan Kualitas Tanah Di Lahan Pertanian - Zega, Krisnawati; Ziliwu, Fince Mega Ceria (CV. SINAR HOWUHOWU, 2024)
The increasing global demand for food amidst increasingly extreme climate change poses significant challenges to the agricultural sector, particularly in arid lands vulnerable to drought. Unsustainable water use and improper irrigation practices can negatively impact the physical and chemical properties of soil, threatening agricultural productivity and sustainability. This study aims to analyze the influence of various irrigation practices on the physical and chemical properties of soil in dryland agricultural areas. The research methodology includes measuring physical soil properties such as texture, structure, and water holding capacity, as well as chemical soil analysis to determine salinity levels and nutrient availability. This research investigates the impact of irrigation water use on the physical and chemical properties of agricultural land in Village Afia, District Nort Nias, using a qualitative approach. Data was collected through participant observation, in-depth interviews with farmers, and analysis of documents related to irrigation practices. The research results indicate a correlation between irrigation patterns and soil conditions. Excessive irrigation water use is associated with increased soil salinity and decreased soil structure, while well-managed irrigation contributes to improved soil fertility. This study highlights the importance of sustainable irrigation management to maintain soil quality and agricultural productivity.